2021
DOI: 10.3390/ijerph19010174
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity and Collective Self-Esteem Mediate the Effect of Anxiety and Depression on Quality of Life in a Migrant Population

Abstract: Migration processes can often trigger negative interactions with the context, generating problems in both the physical and mental health of migrants, which have an impact on both their well-being and their quality of life. In this framework, the research aimed to assess the mediating effect of ethnic identity and collective self-esteem on the inverse relationship between mental health problems and quality of life. Data were collected from 908 first-generation Colombian migrants living in Chile, of whom 50.2% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Firstly, positive campus characteristics such as good teacher-student relationships, sound infrastructures and fair systems promote a higher sense of belonging to the school, making students feel part of the school, more aware of their importance and value in their group, hold more positive evaluations of the school and show higher levels of collective self-esteem [ 65 ]. Secondly, anxiety is an important emotional manifestation of academic burnout, and self-esteem is an important force in reducing anxiety [ 26 , 77 ]. Individuals with high collective self-esteem are more likely to have a positive emotional experience of school, maintain a good emotional state even when suffering from chronic academic stress, seek social support to alleviate anxiety, and engage in learning with a positive attitude, thereby reducing academic burnout [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, positive campus characteristics such as good teacher-student relationships, sound infrastructures and fair systems promote a higher sense of belonging to the school, making students feel part of the school, more aware of their importance and value in their group, hold more positive evaluations of the school and show higher levels of collective self-esteem [ 65 ]. Secondly, anxiety is an important emotional manifestation of academic burnout, and self-esteem is an important force in reducing anxiety [ 26 , 77 ]. Individuals with high collective self-esteem are more likely to have a positive emotional experience of school, maintain a good emotional state even when suffering from chronic academic stress, seek social support to alleviate anxiety, and engage in learning with a positive attitude, thereby reducing academic burnout [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…South America and Chile in particular are no exception, with migrants in the latter constituting 7.8% of the country’s total population (INE, 2021 ), the largest percentage coming from other Latin American countries, with Venezuelan migration being the main one in the last 10 years (DEM, 2021 ). Despite how attractive and hopeful it seems to be to migrate in search of better opportunities, migrating is not easy, since on the one hand one leaves behind family, friends, interpersonal relationships, economic resources, culture, and customs and, on the other hand, once migrants arrive in the host country, being part of a minority group, they often suffer experiences of prejudice and discrimination that negatively affect their health and welfare (Firat, & Noels, 2021 ; Lincoln et al, 2021 ; Urzúa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that some variables related to social identity would have an important influence on the health and well-being of migrants (Balidemaj & Small, 2019 ; Espinosa & Tapia, 2011 ; Haslam et al, 2009 ; Luhtanen & Crocker, 1992 ; Phinney et al, 2001 ; Urzúa et al, 2022 ). Social identity has traditionally been defined as an individual’s knowledge that he or she belongs to certain social groups along with some emotional and value meaning to him or her of group membership (Tajfel, 1972 ).…”
Section: Introductionmentioning
confidence: 99%